URANIUM-TITANIUM-METAGEL MINERALIZATION OF AU-U DEPOSITS OF THE ELKON ORE DISTRICT (ALDAN, RUSSIA) AND FEATURES OF ITS PROCESSING - A. P. Aleshin; V. D. Kozyr’Kov; K. M. Smirnov; VL. B. Komarov; M. M. Ivanchenko; VIKT. B. Komarov; I. G. Griboedova (Известия высших учебных заведений: Геология и разведка, 2016)
Large-scale reserves of uranium in Au-U deposits of the Elkon ore district are composed of newly discovered polyphase uranium-titanium metagel (UTM). Before, it was assumed that brannerite is the major mineral of these ores. However, it has been revealed that brannerite and uranium oxides and silicates are minor components of mineralization. Succession of UTM phases selection, their relations with brannerite are characterized. Few groups of UTM has been revealed by composition of major and trace elements. The filter cake of acidic leaching of a technological sample with residual uranium concentration of 0,02 wt.% and grain size of -0.16 mm was investigated. As it was established, the major part of uranium is in the fine grained UTM phases submerged in quartz-feldspar matrix of the cake particles. Taking into account a small size of the uranium phases (first microns, rarely n-10 mkm), recrusing of the ore to smaller grades will unlikely lead to a noticeable uranium yield into final product.